Resource Sharing in Continuous Sliding-Window Aggregates - Arasu, Arvind; Widom, Jennifer (Proceedings of the 30th International Conference on Very Large Data Bases (VLDB 2004), 2004)
We consider the problem of resource sharing when processing large numbers of continuous queries. We specifically address sliding-window aggregates over data streams, an important class of continuous operators for which sharing has not been addressed. We present a suite of sharing techniques that cover a wide range of possible scenarios: different classes of aggregation functions (algebraic, distributive, holistic), different window types (time-based, tuple-based, suffix, historical), and different input models (single stream, multiple substreams). We provide precise theoretical performance guarantees for our techniques, and show their practical effectiveness through experimental study.